Deep water, an effect on the temperature for the management of caligodosis in the Atlantic salmon (Salmon salar) - Riquelme, Roberto (2017)
Salmon farming is one of the pillars of the Chilean economy but due the emerging of many diseases, including the ecto-parasitism caused by Caligus rogercresseyi, the salmon industry has decreased their production indices. Based on that, alternative rearing systems are being evaluated for salmon cultivation, one of them fish farming in deep water, where the temperature is lower than the temperature of the surface, as C. rogercresseyi is a parasite whose life cycle is water temperature dependent. This paper describes the biological behaviour of the parasite and the effect of deep water and culture temperature on the establishment of the parasite in the host.